Ultraviolet Light‐Assisted Electrospinning of Core–Shell Fully Cross‐Linked P(NIPAAm‐co‐NIPMAAm) Hydrogel‐Based Nanofibers for Thermally Induced Drug Delivery Self‐Regulation. Issue 12 (4th May 2020) - Pawłowska, Sylwia; Rinoldi, Chiara; Nakielski, Paweł; Ziai, Yasamin; Urbanek, Olga; Li, Xiaoran; Kowalewski, Tomasz Aleksander; Ding, Bin; Pierini, Filippo
Abstract: Body tissues and organs have complex functions which undergo intrinsic changes during medical treatments. For the development of ideal drug delivery systems, understanding the biological tissue activities is necessary to be able to design materials capable of changing their properties over time, on the basis of the patient's tissue needs. In this study, a nanofibrous thermal‐responsive drug delivery system is developed. The thermo‐responsivity of the system makes it possible to self‐regulate the release of bioactive molecules, while reducing the drug delivery at early stages, thus avoiding high concentrations of drugs which may be toxic for healthy cells. A co‐axial electrospinning technique is used to fabricate core–shell cross‐linked copolymer poly( N ‐isopropylacrylamide‐ co ‐ N ‐isopropylmethacrylamide) (P(NIPAAm‐ co ‐NIPMAAm)) hydrogel‐based nanofibers. The obtained nanofibers are made of a core of thermo‐responsive hydrogel containing a drug model, while the outer shell is made of poly‐l ‐lactide‐ co ‐caprolactone (PLCL). The custom‐made electrospinning apparatus enables the in situ cross‐linking of P(NIPAAm‐ co ‐NIPMAAm) hydrogel into a nanoscale confined space, which improves the electrospun nanofiber drug dosing process, by reducing its provision and allowing a self‐regulated release control. The mechanism of the temperature‐induced release control is studied in depth, and it is shown that the system is a promising candidate as a "smart" drug delivery platform. Abstract : A stimuli‐responsive nanoplatform for self‐regulated drug delivery is developed confining a fully cross‐linked poly( N ‐isopropylacrylamide‐ co ‐ N ‐isopropylmethacrylamide) hydrogel within the structure of electrospun core–shell nanofibers. The nanostructure shows a biomimetic architecture capable of enhancing the interaction with cells and the possibility to adjust the biomolecule delivery, limiting release at the first stage and prolonging it over time by using a temperature‐regulated mechanism.